Evaluation and perioperative management of patients with diabetes mellitus. A challenge for the anesthesiologist - Pontes, João Paulo Jordão; Mendes, Florentino Fernandes; Vasconcelos, Mateus Meira; Batista, Nubia Rodrigues (Brazilian Journal of Anesthesiology (English Edition), 2018)
Diabetes mellitus (DM) is characterized by alteration in carbohydrate metabolism, leading to hyperglycemia and increased perioperative morbidity and mortality. It evolves with diverse and progressive physiological changes, and the anesthetic management requires attention regarding this disease interference in multiple organ systems and their respective complications. Patient’s history, physical examination, and complementary exams are important in the preoperative management, particularly glycosylated hemoglobin (HbA1c), which has a strong predictive value for complications associated with diabetes. The goal of surgical planning is to reduce the fasting time and maintain the patient’s routine. Patients with Type 1 DM must receive insulin (even during the preoperative fast) to meet the basal physiological demands and avoid ketoacidosis. Whereas patients with Type 2 DM treated with multiple injectable and/or oral drugs are susceptible to develop a hyperglycemic hyperosmolar state (HHS). Therefore, the management of hypoglycemic agents and different types of insulin is fundamental, as well as determining the surgical schedule and, consequently, the number of lost meals for dose adjustment and drug suspension. Current evidence suggests the safe target to maintain glycemic control in surgical patients, but does not conclude whether it should be obtained with either moderate or severe glycemic control.